De l’utile et de l’agréable : un jardin romain chez les Pictons. La Viaube 1 à Jaunay-Clan (Vienne) - Gaëlle Lavoix; Frédéric Gerber; David Guitton (Gallia)
A preventive archaeological excavation realized in 2010 in Jaunay-Clan, near Poitiers (Vienne), revealed the existence of a large horticultural estate from the beginning of the 1st century AD, which surface is estimated at almost seven hectares. A ditches network, horticultural pots and chequered plantation pits are near a dug composition previously unseen in Gaule: the “sanctuaire” végétal. With a very elaborated plan, this composition hardly seems to find its place into a space whose vocation would be – or would only be – productive. On the contrary it has currently analogies only with spaces which use is clearly ostentatious and oriented toward owners’ pleasure: parks and gardens of luxurious italic villae.